Haemodynamic Responses to Tracheal Intubation Using Propofol, Etomidate and Etomidate-Propofol Combination in Anaesthesia Induction - Özgür Yağan; Nilay Taş; Ahmet Küçük; Volkan Hancı; Bülent Yurtlu (Journal of Cardiovascular and Thoracic Research, 2015)
Introduction: The aim of this study was to measure the haemodynamic responses to a etomidate-propofol combination used for anaesthesia induction and to compare the haemodynamic responses with the separate use of each drug. Methods: The patients were randomly divided into three groups as group P (n=30, propofol 2.5 mg kg-1), group E (n=30, etomidate 0.3 mg kg-1) and group PE (n=30, propofol 1.25 mg kg-1 + etomidate 0.15 mg kg-1). For each patient, the times of measurement of the heart rate (HR) and mean arterial pressure values were defined as baseline, after the induction, before the intubation, immediately after the intubation and 1, 2, 3, 4, 5 and 10 minutes after the intubation. Results: In all 3 groups, a significant decrease in MAP values were seen at T2 and T3 compared to the baseline values, and this decrease was greater in group P compared to that in group E and PE (P<0.001, P<0.01). A significant increase was seen in all 3 groups in the mean arterial pressure (MAP) value at T4 after the intubation. When the groups were compared with each other, this increase was greater in group E than in the other two groups (with group P, P<0.001; with group PE, P<0.01). Conclusion: Etomidate-propofol combination may be a valuable alternative when extremes of hypotensive and hypertensive responses due to propofol and etomidate are best to be avoided.